Beyond the Monitor: How Immersion can Transform (and Complicate) User Satisfaction - Peres, Fabiana; Nunes, Fátima; Teixeira, João Marcelo; Domingues, Gustavo; Zanellatto, Letícia; Macedo, José; Maurício, Claudio (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Immersive virtual reality holds the potential to provide a safe and efficient environment for the education and training of invasive healthcare procedures. Nevertheless, some tasks or users may present additional challenges. This work examines whether an HMD adds measurable value to a simulator in health area to train dental anesthesia, when compared with its conventional desktop counterpart. Twenty-four participants completed two full training runs in each platform (desktop, HMD). We logged phase-specific and total task times, collected SUS, UEQ and SSQ scores for both conditions, and recorded participants’ ranked preference. Motion-sickness history, visual limitations and prior VR experience were surveyed as well. Statistical treatment combined parametric/non-parametric tests and correlations; qualitative remarks were thematically coded. Task duration in HMD version was longer in 71 % of sessions. Neither UEQ nor SUS differentials explained VR environment preference; SSQ scores were low overall and unrelated to the type of VR environment used. Most users without visual impairment preferred the HMD version, yet the association missed significance. Open comments about HMD version praised greater immersion, realism and pedagogical value, while pinpointing friction in fine motor tasks, lack of visual guides, sporadic lag and eyestrain.